The Concept of Heritage Richness and Identity in The Design Confirmity Study of The Three Palembang Mosques: Muara Ogan Mosque/Ki Marogan, Lawang Kidul Mosque, and Ki Gede Ing Suro Mosque, in Relation to The Hadith of Bukhari-Muslim - Arief, Abdurrachman; Prima, Listen (Sinektika: Jurnal Arsitektur, 2026)
Mosques, as central religious architecture in Islam, serve a dual function: as places of worship and centres for community social activities. The evolving nature and diversity of mosque architectural typologies, both in Indonesia and globally, underscore the urgent need for establishing systematic design principles. This research compiles a set of mosque design principles based on relevant interpretations from the Hadith of Bukhari and Muslim. These principles can be applied as prescriptive guidelines for designing new mosques and as an evaluative framework for analysing existing structures. This framework is then integrated with survey findings from the case studies. The case studies focus on three historical mosques in Palembang, South Sumatra: Masjid Ki Marogan (established 1890), Masjid Lawang Kidul (established 1890), and Masjid Suro (established 1889). The selection of these sites is based on their significance as representations of the richness and heritage identity of sustained local Islamic architecture in Palembang. The research methodology employed is a comprehensive field survey, involving the identification and analysis of architectural elements (physical form, spatial layout, and functional activities) against the formulated design principles. The research findings will identify the degree of conformity between the actual conditions of these mosques and the proposed principles. The practical implications of these findings are expected to provide substantive recommendations for mosque management in planning and construction, ensuring that the buildings not only meet functional and religious aspects but also preserve their historical value and strengthen the inherent heritage identity of these three mosques.